FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH SEBAGAI UNSUR PENYELENGGARA PEMERINTAH DAERAH BERDASARKAN UNDANG – UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Elita Tampubolon; Ranap Sitanggang; Haposan Siallagan (LPPM Universitas HKBP Nommensen, 2020)
Regional people's representatives council or abbreviated as DPRD is a representative positioned as an element of provincial/regencial administration in Indonesia.This council is directly elected by the society as the representation to take part in government implementation. the problems caused among the society are not the measurement that DPRD not organize its funtions but this is to help DPRD as the representative of society in administrating the local government.